Direct Banking - A Demand Pull and Technology Push Innovation - Doris Neuberger (Universität Rostock, Institut für Volkswirtschaftslehre, 1997)
Since 1994, the German banking market is confronted with an entry wave of direct banks. This banking innovation may be explained by developments on the supply side as well as on the demand side. It is pushed by developments in telecommunication technologies during a period of rising cost competition and pulled by a change in the demand for selling efforts by banks. Within a model of monopolistic competition with endogenous selling efforts we show that in the long run, a direct banking market supports a larger number of firms which offer their products at lower prices than a branch banking market. If customers are heterogeneous, both banking types will survive.
Keywords: 330; Bankmarketing; Direktmarketing; Electronic Banking; Innovation; Monopolistischer Wettbewerb; Theorie; Deutschland; Bank